Estimation of visitors' preferences for house boat service attributes by using a choice experiment - Wan Mohamad, Wan Norhidayah; Radam, Alias; Yacob, Mohd Rusli (Faculty of Economics and Management, Universiti Putra Malaysia, 2012)
This paper aims to capture the level of satisfaction of the visitors towards the ecotourism service attributes at Kenyir Lake, by providing results of a valuation study on the house boat services, which is the main focus in the research. A choice experiment is employed to estimate the visitors’ preferences for houseboat service attributes. The attributes investigated were tourist guide (TG), provision of safety equipment (SAFE), coverage for communication system (COMM), package of activities (ACTV) and extra package price (EPP). The simple conditional logit (CL) model is estimated to identify the preferences of the visitors from various service options of house boat attributes. Finding of this study can assist house boat operators and policy makers in order to identify the real concerns and issues which could be useful for the development and improvement of house boat services and the implementation of relevant policies that appropriate with the current service condition.